Current Practice and Attitudes of Australian Obstetricians Toward Population-Based Carrier Screening for Inherited Conditions. (21st January 2013) - Stark, Zornitza; Massie, John; McClaren, Belinda; Ioannou, Liane; Cousens, Nicole; Lewis, Sharon; Metcalfe, Sylvia; Delatycki, Martin B.
Abstract : An anonymous survey of Australian Fellows of the Royal Australian and New Zealand College of Obstetricians and Gynaecologists was conducted with the aim of understanding current practice and attitudes toward population-based carrier screening for inherited conditions in the setting of routine pregnancy care. Of 1, 121 Fellows invited to complete the online questionnaire by e-mail, 237 (21%) responded, and of these 156 were practicing obstetricians and completed the whole survey. Of the respondents, 83% expressed support for population-based carrier screening for at least some conditions, with 97% supporting carrier screening for β-thalassaemia, and 83% supporting carrier screening for cystic fibrosis (CF). A small proportion of obstetricians reported offering carrier screening as part of routine pregnancy care (20% for β-thalassaemia, 8% for CF, 5% for fragile X syndrome, and 2% for spinal muscular atrophy). The main practical barriers identified for screening were cost, time constraints, and availability of supporting services. Addressing these issues is crucial for the successful implementation of population-based carrier screening programs in Australia and internationally.